THE DIFFERENCES MUSCULOSKELETAL DISORDER BETWEEN WOOD CARVERS AND PAINTERS IN UBUD - Patmala, Ni Kadek Citra; Dewi, Anak Ayu Nyoman Trisna Narta; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 3 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT   Work activity can cause pain, pain, stiffness and other disorders of the muscular system which is one of the musculoskeletal complaints. Wood carvers and painters are workers who still dominant work with the manual system.The purpose of this study was to know the difference of musculoskeletal disorder between woodcarvers and painters and to justify the hypothesis of purpose that has been formulated.This research was observational research, categorical analytics unpaired with cross sectional approach. Sampling technique in this research was simple random sampling. The sample of this study amounted to 96 people divided into 2 groups, namely groups of wood carvers and painters. Data collection was done by filling the Nordic Body Map questionnaire. Statistical test using Chi-Square and Independent T-test. The results showed significant differences in musculoskeletal disorder on wood carver and painter, with  woodcarvers mean value of 40,7 ± 5,3 and painters mean value of 43,2 ± 6,2, so p = 0,038 (p <0,05) , then there are differences in musculoskeletal disorder among woodcarvers and painters, where musculoskeletal disorders at greater painter than woodcarver. Analysis of the difference each extremity musculoskeletal disorders in the upper extremities get results with woodcarvers mean value of17.1 ± 0.38 and painters mean value of 17,3 ± 2,5, so p= 0,692 (p> 0,05), on the trunk with woodcarvers mean value of 8,3 ± 1,69 and painters mean value of 10,5 ± 2,50, so p = 0,000 (p <0,05) and in the lower extremities with woodcarvers mean value of 15,1 ± 2,69 and the average value of the painters 15.1 ± 3.33, so p = 0.973 (p> 0.05). The results of the analysis of each extremity musculoskeletal disorders in woodcarvers and painters, it can be concluded that there are significant differences in musculoskeletal disorder among woodcarvers and painters on the trunk and there are no significant differences in musculoskeletal disorder among woodcarvers and painters in the upper extremities and the lower extremities.   Keywords:   muskuloskeletal disorder, Nordic body map, wood carver, painter